Unformatted text preview: 1 ∆ X + β 3 ∆ X = ( β 1 + β 3 ) ∆ X The expected change in Y when X changes by ∆ X and D = 0 is: ∆ Y = β + β 1 ( X + ∆ X ) − β − β 1 X = β 1 ∆ X (b) From ( a ) , we can say that this happens when β 3 = 0 (c) When D = 1 , the population regression function is: E ( Y i  X i , D i = 1) = β + β 1 X i + β 2 + β 3 X i = ( β + β 2 )+( β 1 + β 3 ) X i When D = 0 , the population regression function is: E ( Y i  X i , D i = 0) = β + β 1 X i (d) From ( c ) , we can say that this happens when β 2 = 0 and β 3 = 0 . 1...
View
Full Document
 Fall '08
 Staff
 Econometrics, Linear Regression, Regression Analysis, Errors and residuals in statistics, DI, ui  Xi

Click to edit the document details